Internalisasi Karakter Kemandirian Dalam Mata Pelajaran Pendidikan Agama Islam Di SMP N 2 Babat Lamongan - Rokim Rokim; Abd. Manan (Akademika, 2022)
In the current era of globalization, problems related to independence are still frequently encountered in the surrounding environment, including in the educational environment. Like, lack of independence in students will result in students having a tendency to depend on others, lack of creativity, laziness, lack of confidence and unable to solve their own problems. And one alternative that can be used as an instrument is to internalize the character of independence by optimizing the learning of Islamic Religious Education (PAI) material. This research aims to find out about: 1) process of learning the character of independence in Islamic Religious Education subjects in SMP N 2 Babat Lamongan, 2) process of habituation of character learning in independence in Islamic Religious Education subjects in SMP N 2 Babat Lamongan, 3) actualization of the character of independence in Islamic Religious Education subjects in SMP N 2 Babat Lamongan. Research using this qualitative method has concluded, among others: 1) The process of learning the character of independence, PAI teachers have internalized the value of independence character to students in the learning process of PAI, 2) The process of habituating the character of independence, PAI teachers internalize through programmed activities in learning or not programmed in the daily activities of students in the school environment., 3) actualizing of the character of independence, students have implemented variously. However, there are many students who apply the value of independence characters only some students have not applied the value of independence characters.